Adherence to Psychostimulant Medication in Children with Attention-Deficit/Hyperactivity Disorder: The Role of Attitudes - Hébert, Julien (Canadian Academy of Child and Adolescent Psychiatry, 2013)
OBJECTIVE: To investigate how attitudes towards psychostimulant medication influence the adherence to psychostimulant treatment in children with Attention-Deficit/Hyperactivity Disorder (ADHD). METHOD: Thirty-three children with ADHD were prospectively recruited to take part in this study. The children and their parents filled questionnaires at both baseline and at a three-month follow-up to assess the severity of ADHD symptoms in the child and attitudes towards psychostimulant medication. Adherence to medication was assessed through standardized interviews of parents. RESULTS: Parental perceived psychosocial benefits of psychostimulant medication at the three-month follow-up were found to be positive predictors of adherence to medication. Parental perceived psychosocial benefits of medication at the three-month follow-up was in turn predicted by parental medication acceptability at three months and child’s perceived psychosocial benefits of medication at three-months. CONCLUSION: Improving parents’ awareness of psychosocial benefits of psychostimulant medication may increase adherence to psychostimulant medication in children with ADHD. Age of the child and severity of symptoms did not significantly affect medication adherence.